Knowledge Sharing and Its Impact on Organizational Performance- An Analytical Study in the Directorate of Education, AL- Karkh First, Baghdad - Hafedh Farhan, Mohammed; Yaseen Raheem, Mohammed (Journal of Economics and Administrative Sciences, 2024)
Purpose: The current research aims to identify the impact of knowledge sharing on organizational performance with a sample in the Ministry of Education/ the Directorate of Education of First Karkh.Theoretical framework: Knowledge sharing is one of the key factors that contribute to improving organizational performance through exchanging of knowledge and experiences among employees. It highlights the importance of this process in developing and improving performance in a changeable environment.Design/methodology/approach: This study was conducted in the Directorate of Education, First Karkh, Baghdad, with 187 legitimate questionnaires that were analyzed using  superior statistical techniques.Findings: Knowledge sharing significantly influences organizational performance and confirms both main hypotheses and sub-hypotheses.Research, Practical & Social implications: Recommendations include improving training programs, encouraging collaboration, motivating employees through rewards, and encouraging technology sharing.Originality/value: This research emphasizes the important role of knowledge sharing in improving organizational performance within the business sector. It provides valuable insights into how e adopting knowledge sharing practices can strengthen productivity and crisis management in the Iraqi context.